Predictors of risky health behaviours among secondary school students with hearing Impairment (2015)
Like every adolescent, students with hearing impairment engaged in Risky Health Behaviour (RHB) such as alcohol consumption, cigarette consumption, drug abuse, inadequate physical activities, unhealthy dietary behaviour as well as indiscriminate sexual acts. These activities have therefore become issues of public health concern. Previous studies have focused majorly on the academic performance, emotional stability and psychological adjustment of students with hearing impairment than on their RHB and its socio-economic predisposing factors. This study, therefore, examined social (discrimination, home, health awareness, peer influence and false belief) and economic (poverty and purchasing power) factors as predictors of RHB among Secondary School Students with Hearing Impairment (SSSHI) in south-west, Nigeria. The study adopted a descriptive survey design. Purposive sampling technique was used to select 980 students with hearing impairment from some secondary schools in southwest Nigeria. Five hypotheses were tested at 0.05 level of significance. Data was analysed using descriptive statistics, multiple regression. Social and economic factors had significant composite contribution to RHB (F(7,973)=22.80; R=0.37) and accounted for 17.0% of the variance of RHB. The relative contributions of the independent variables to risky health be behaviour are: Peer influence (P=0.25), Purchasing power (P=0.23), discrimination (0.15), poverty (P=0.10) home (P=0.08), false belief (P=0.07) and health awareness (0.02). Unfriendly home situation, negative peer influence, false beliefs, poverty and low purchasing power predicted risky health behaviour among secondary school students with hearing impairment. Therefore, government should organise periodic health and sensitization programmes on health issues for students, parents and teachers.